Predictors in the quality of life of the elderly: A systematic review - Melissa Sánchez Rodas; Arturo Enrique Orozco Vargas; Brenda Sarahi Cervantes Luna; María del Consuelo Escoto Ponce de León (Revista de Psicología y Ciencias del Comportamiento de la Unidad Académica de Ciencias Jurídicas y Sociales)
The construct of quality of life (QoL) is closely related to population aging and to biological, psychological, social, and spiritual changes. In turn, living longer does not mean living with QoL, so it is important to study the various predictors of QoL in old age. The objective of this systematic review was to analyze the existing information on clinical variables in relation to QoL in older people (PM). Included were papers published between 2018 and 2023 in Google Scholar, MEDLINE-ProQuest, EBSCOhost, with a population aged 60 years or older, articles in English, Spanish or Portu-guese, and cross-sectional and/or longitudinal stu-dies. The sample consisted of 16 original articles, showing that most of the studies focused on the relationship between family functioning and QoL. In contrast, the minority were with the variables of physical fitness, psychological well-being and emotional intelligence. It was observed that some studies did not use a significant population, which limited the knowledge of these variables.